Performance Assessment of Integrated Water Quality Monitoring Device with IoT Technology for Water Quality Monitoring - Muhammad Izz Hakimi Zaidi Farouk; Zadariana Jamil; Mohd Fuad Abdul Latip; Nur Kamaliah Mustaffa; Azianabiha A. Halip; Normaliza Noordin; Yahzam Muhamad; Nik Norazlina Che Ya (International Journal of Integrated Engineering, 2025)
A continuous water supply is a vital resource for domestic use and environmental sustainability, necessitating effective water management. Frequent water quality disruptions caused by river contamination have harmed aquatic life and led to shutdowns of water treatment plants, affecting consumers. The implementation of continuous online monitoring can facilitate early detection of contamination. The research focuses on the performance assessment of an integrated online water quality monitoring (IWQM) prototype (named Kolora meter) assisted with Internet of Things (IoT) technology. The IWQM prototype features seven water quality sensors, namely pH, dissolved oxygen (DO), conductivity (EC), total dissolved solids (TDS), temperature (T), turbidity (TUR), and volatile organic compound (VOC) gas, to monitor surface water. Additionally, the IWQM prototype was equipped with a mobile application, which was developed on the Blynk IoT platform. This enables the user to monitor wirelessly via smartphone or computer. This prototype was deployed and tested at Putrajaya Lake (Point 1) and Wetland (Point 2) for one month to determine its efficiency and reliability. The issues experienced during the field deployment period were identified. The data measured by the IWQM prototype was compared and validated using the data collected from a Horiba Multiparameter. The T sensor showed consistent readings with high accuracy ( 0 to 7%) while pH and DO showed inconsistent readings and accuracy. Unfortunately, the TDS, TUR, and EC could not be measured during the field deployment test due to sensor and hardware failures. The issues and mitigation strategies of the IWQM prototype have been discussed and highlighted for future improvement in the development of online water quality monitoring devices.